Site-Specific DC Surface Signatures Influence CD4+ T Cell Co-stimulation and Lung-Homing - Pejoski, David; Ballester, Marie; Auderset, Floriane; Vono, Maria; Christensen, Dennis; Andersen, Peter; Lambert, Paul-Henri; Siegrist, Claire-Anne (Frontiers in Immunology, 2019)
Dendritic cells (DCs) that drain the gut and skin are known to favor the establishment of T cell populations that home to the original site of DC-antigen (Ag) encounter by providing soluble ‘imprinting’ signals to T cells in the lymph node (LN). To study the induction of lung T cell-trafficking, we used a protein-adjuvant murine intranasal and intramuscular immunization model to compare in vivo-activated Ag+ DCs in the lung and muscle-draining LNs. Higher frequencies of Ag+ CD11b+ DCs were observed in lung-draining mediastinal LNs (MedLN) compared to muscle-draining inguinal LNs (ILN). Ag+ CD11b+ MedLN DCs were qualitatively superior at priming CD4+ T cells that then expressed CD49a+ CXCR3+ and preferentially trafficked into the lung parenchyma. CD11b+ DCs from the MedLN expressed higher levels of surface podoplanin, Trem4, GL7, and the known co-stimulatory molecules CD80, CD86, and CD24. Blockade of specific MedLN DC molecules or the use of sorted DC and T cell co-cultures demonstrated that DC surface phenotype influences the ability to prime T cells that then home to the lung. Thus, the density of dLN Ag+ DCs, and DC surface molecule signatures, are factors that can influence the output and differentiation of lung-homing CD4+ T cells.